Blood pressure measurement in the United Kingdom Heart Disease Prevention Project. Issue 4 (December 1978) - Heller, R F; Rose, G; Pedoe, H D; Christie, D G
Abstract : A blood pressure measurement was part of a cardiovascular screening examination of 8397 middle-aged men taking part in the intervention section of the United Kingdom Heart Disease Prevention Project. Standardised training techniques reduced observer bias to acceptable limits in four out of a total of five observers. The time of day and room temperature both made significant differences to the blood pressure measurement. High room temperatures in particular apparently had a marked effect in reducing the level of blood pressure. There were consistent and large positive associations with increasing age and overweight. The survey revealed a poor degree of blood pressure control in the community at the time of screening--only 7% of the "hypertensive" population had their diastolic pressure controlled to below 100 mm Hg.